THE CORRELATION BETWEEN THE MERDEKA CURRICULUM AND TEACHING CHALLENGES IN THE DIGITAL ERA IN INDONESIAN SECONDARY SCHOOLS: QUALITATIVE ANALYSIS STUDY - Andi Muh Akbar Saputra; Pandu Perdana Putra; Imam Prawiranegara Gani; Iut Nuraini, Fitria Hansyah Fatmasari (Adisam Publisher, 2023)
This abstract provides a concise overview of the research on the intersection between the Merdeka Curriculum and teaching challenges in the digital era in Indonesian secondary schools. Implementing the Merdeka Curriculum in Indonesian secondary schools coincides with the evolving landscape of education in the digital era. This research explores the intersection of these two factors, aiming to understand how the curriculum aligns with and addresses the teaching challenges posed by the digital era. Through qualitative research methods, including interviews with educators, document analysis, and surveys of secondary school students, this study examines the impacts, challenges, and opportunities presented by the Merdeka Curriculum in the context of the digital age. Preliminary findings suggest that the Merdeka Curriculum has positively influenced students' critical thinking and civic awareness. However, educators report challenges related to students' overreliance on digital devices, digital literacy, and the need to balance national identity with global perspectives. The research offers practical implications for curriculum development and policy recommendations to foster digital literacy, maintain a focus on critical thinking, and find a harmonious balance between national and global perspectives. This study contributes to the ongoing discourse on curriculum adaptation to meet the demands of the digital era in Indonesian secondary education.